Development of a model for optimal configuration components selection for architecture of critical IT infrastructure at its designing - Dorogyy, Yaroslaw (Technology audit and production reserves, 2017)
The object of research is a critical IT infrastructure. One of the most problematic places in the study of critical IT infrastructures is the complete lack of approaches, methodology and tools for designing, modeling and researching critical IT infrastructures that could be used in the form in which they are offered. Based on the Markov decision-making process, a model is proposed that will allow to evaluate the implementation options for components, critical IT infrastructure systems by various criteria. The peculiarity of this model is the use of an extended set of criteria, which makes it possible to evaluate the implementation options for components and systems of critical IT infrastructure from different points of view. In the course of the research, MatLab software package is used, which allowed to check the proposed model for operability. The resulting model is fairly compact and fully reflects the necessary logic for evaluating the implementation options for components and critical IT infrastructure systems. It is shown that this is achieved due to the flexibility of the proposed mathematical apparatus, namely the possibility of using different evaluation criteria. In the future, the proposed model and assessment models for all major systems and critical IT infrastructure components will provide a convenient tool for a wide range of researchers whose work is related to all aspects of researching critical IT infrastructures. As a result of modeling, among the 84 possible configurations of the data processing center, the best overall winning (configuration 4) is chosen.